Spatial modelling of urban change using satellite remote sensing: a review (2013)
Urbanization is one of the most evident human-induced global changes. Population growth is an important factor that contributes to change in any urban system. Although urbanization has been an issue of concern, its rate is of a more serious concern. Despite its economic importance, urban growth has a considerable impact on the surrounding environment. Addressing the various challenges posed by urbanization process requires spatio-temporal analysis of cities and regions. This is because cities are dynamic so also are the processes that are shaping cities globally and locally. Researchers and city planners have assessed urbanization processes through the lens of remote sensing and Geographic Information System (GIS). Recent advances in RS and GIS tools with varying analysis techniques have enabled researchers to model urban change effectively. Using a critical review approach, this paper contributes to the growing bodies of knowledge by reviewing published studies that made use of satellite RS and GIS in understanding the dynamism of urban areas through change detection and urban modelling.